1969
DOI: 10.1111/j.1570-7458.1969.tb02557.x
|View full text |Cite
|
Sign up to set email alerts
|

Food Attractants and a Pheromone as Trail‐following Substances for the Saintonge Termite

Abstract: Column chromatography of the unsaponifiable lipids from pine wood, on which the fungus Lenzites trabea was cultured, yielded two well‐separated fractions, which were highly active in choice tests as well as in a trail‐following test with the termite Reticulitermes lucifugus var. santonensis (Feytaud). Thin layer and gas chromatography confirmed that these fractions contained distinctly different active compounds. Column chromatography of the non‐saponifiable lipids of the worker termites yielded only one activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1971
1971
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Trail‐following pheromones of termites were demonstrated for the first time using the ‘one‐piece’ termites Zootermopsis and Kalotermes (Lüscher & Müller, 1960; Stuart, 1961). The existence of trail‐following pheromones in termites whose individuals do not forage away from the nest was questioned (Ritter & Coenen‐Saraber, 1969), but Stuart (1963, 1967, 1969) suggested that the pheromone served as an alarm signal eliciting the excitation and recruitment to sources of disturbance within the nest. In fact, pseudergates of Zootermopsis also use trail‐following pheromones to build external galleries (Bordereau & Pasteels, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Trail‐following pheromones of termites were demonstrated for the first time using the ‘one‐piece’ termites Zootermopsis and Kalotermes (Lüscher & Müller, 1960; Stuart, 1961). The existence of trail‐following pheromones in termites whose individuals do not forage away from the nest was questioned (Ritter & Coenen‐Saraber, 1969), but Stuart (1963, 1967, 1969) suggested that the pheromone served as an alarm signal eliciting the excitation and recruitment to sources of disturbance within the nest. In fact, pseudergates of Zootermopsis also use trail‐following pheromones to build external galleries (Bordereau & Pasteels, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This study, therefore, investigates in the termite species R. santonensis foraging and recruitment patterns on colony level as well as the behaviour of individual termites during the search for food. This species is indigenous in the Saintonge region in France (Ritter and Coenen-Saraber, 1969).…”
Section: Introductionmentioning
confidence: 99%